ANALISIS HUKUM ISLAM TERHADAP HUBUNGAN BADAN SUAMI ISTRI DALAM MASA KAFARAT ZHIHAR - Siti Mar’atus Shoolihan; Fashihuddin Arafat (Institut Keislaman Abdullah Faqih Gresik, 2021)
Zhihar means that a husband equates his wife with his mahram in matters relating to sexual relations. As the husband said: